2020
DOI: 10.1177/1090198120931788
|View full text |Cite
|
Sign up to set email alerts
|

Nudging in Public Health Lifestyle Interventions: A Systematic Literature Review and Metasynthesis

Abstract: Nudging is increasingly used in public health interventions in Western societies to produced health-promoting behavior changes; however, there is lack of clarity as to what constitutes a nudge, scant knowledge of the effectiveness of nudging techniques in public health lifestyle interventions and a number of ethical and value-based concerns. The aim of this review is to address these research lacunae and identify the characteristics of nudges in empirical research on public health interventions intended to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 113 publications
0
41
0
4
Order By: Relevance
“…Such studies promote understanding of nudging, as they characterise the contours of nudging activities in certain spheres. Empirical studies of nudging have highlighted that some nudges work, at least in experimental contexts, while others (such as nudges to take the stairs) can have the opposite effect (Ledderer et al, 2020). It would be jnteresting to find out if the placement of carrots at the point of payment make any positive difference to sales.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies promote understanding of nudging, as they characterise the contours of nudging activities in certain spheres. Empirical studies of nudging have highlighted that some nudges work, at least in experimental contexts, while others (such as nudges to take the stairs) can have the opposite effect (Ledderer et al, 2020). It would be jnteresting to find out if the placement of carrots at the point of payment make any positive difference to sales.…”
Section: Discussionmentioning
confidence: 99%
“…The successfulness of this "nudging" approach is difficult to assess because the situation quickly escalated to lockdown. More generally, the degree to which nudges are successful is questionable (Ledderer et al, 2020). Furthermore, in a recent systematic literature review, Ledderer et al (2020) concluded that while nudging can effectively produce immediate change, there was little evidence that nudging interventions resulted in lasting behavioral alterations.…”
Section: Awareness and Behavior Changementioning
confidence: 99%
“…While the initial wave of nudging studies targeted mainly the adoption of healthier behaviours during exercise [ 13 , 14 ], eating [ 15 – 17 ] and quitting smoking [ 18 ], nudging is now increasingly being perceived as a policy strategy to improve public services [ 5 , 19 21 ] like the healthcare system [ 22 ].…”
Section: Introductionmentioning
confidence: 99%